Occurrence and clinicolaboratory profile of mycoplasma infection in children hospitalized with lower respiratory tract infection – A prospective study - Jadala, Hareesh Vardhan; K, Raghavendra (Indian Journal of Child Health, 2019)
Background: Mycoplasma pneumoniae (MP) is a common cause of lower respiratory tract infection (LRTI) in children between 5 and 15 years of age. The clinical and laboratory findings are usually non-specific and extrapulmonary manifestations can be devastating. Objectives: The objectives of the study were to study the occurrence, clinical features, and laboratory profile of MP infection in children presenting with LRTI to a tertiary care hospital. Materials and Methods: This was a hospital-based prospective study done in the inpatient department of pediatrics of a tertiary care teaching hospital in South India from November 2014 to April 2016. Children aged 1 month–18 years, admitted with LRTI were included in the study. A pre-tested semi-structured questionnaire was used to collect history. MP infection was confirmed using mycoplasma immunoglobulin M enzyme-linked immunosorbent assay. Clinical and laboratory findings were compared between mycoplasma positive and negative groups. Results: Among a total of 268 children with LRTI, MP infection was diagnosed in 41 children (15.3%). The peak occurrence was in 9–12 years (30%) followed by 6–9 years (25.4%) and 3–6 years (21.7%) age group. MP infection was more common among malnourished (29.4%) than well-nourished children (13.1%). None of the clinical and laboratory parameters were specific for the infection. Extrapulmonary manifestations were not seen in our study. Conclusion: MP infection can occur even in children in 3–6 years age group. The clinical and laboratory findings in MP infection are non-specific necessitating empirical treatment with macrolide antibiotics in children more than 3 years of age. It is more common among malnourished children and extrapulmonary manifestations are rare in our population.